Deep catalytic hydroconversion of straw-derived bio-oil to alkanes over mesoporous zeolite Y supported nickel nanoparticles. (August 2021) - Kang, Yu-Hong; Wei, Xian-Yong; Zhang, Xiao-Qi; Li, Yan-Jun; Liu, Guang-Hui; Ma, Xiang-Rong; Li, Xiao; Bai, Hong-Cun; Li, Zhen-Ni; Yan, Hai-Jun; Zong, Zhi-Min
Abstract: A supported nickle catalyst was prepared by loading ca . 11% of nickel nanoparticles (NNPs) on mesoporous zeolite Y (MZY) and denoted as Ni11% /MZY. A straw was methanolyzed at 300 °C to obtain methanol-soluble portion as a straw-derived bio-oil (SDBO) in the yield of 19.3%. According to the analysis with a gas chromatograph/mass spectrometer, SDBO consists of arenes (7.8%), oxygen-containing organic compounds (82.8%), nitrogen-containing organic compounds (6.3%), and sulfur-containing organic compounds (3.1%). It was subjected to catalytic hydroconversion (CHC) over Ni11% /MZY in n -hexane under 5 MPa of initial hydrogen pressure (IHP) at 160 °C for 16 h. As a result, all the compounds in SDBO were converted to chain alkanes (60.1%) and cyclanes (39.9%). In Ni11% /MZY, uniformly dispersed NNPs and strong Lewis acid sites in the defective crystal texture of MYZ play crucial roles in hydrogenating aromatic rings and removing heteroatoms (HAs), respectively. Benzyloxybenzene (BOB) was used as a lignin-related model compound. The main product from the CHC of BOB over Ni11% /MZY in n -hexane under 5 MPa of IHP at 160 °C for 2 h is methylcyclohexane in the yield of 90.9%, indicating that both hydrogenation of benzene rings and deoxygenation significantly proceeded. After being recycled 4 times, Ni11% /MZY is still active for the CHC of BOB. Graphical abstract: An straw bio-oil was deeply hydrodeoxygenated to alkane-rich clean liquid fuel over Ni11% /MZY under 5 MPa of initial hydrogen pressure (IHP) at 160 °C and the high yields of chain alkanes (CAs, 60.1%) and cyclanes (39.9%) were obtained. Image 1